Pro-vaccination Groups Expressing Hesitant Attitudes: A Cross-Sectional Study About the Difference Between Attitudes and Actual Behavior in Israel - Hijazi, Rana; Gesser-Edelsburg, Anat; Feder-Bubis, Paula; Mesch, Gustavo S. (Frontiers in Public Health, 2022)
Background Vaccines have contributed to the decline in mortality, morbidity, and even the eradication of various infectious diseases. Over time, the availability of information to the public and the request for public involvement in the health decision-making process have risen, and the confidence in vaccines has dropped. An increasing number of parents and individuals are choosing to delay or refuse vaccines. Objectives (1) Identifying hesitant attitudes among pro-vaccination parents; (2) testing the difference between the rate of hesitant attitudes and the rate of hesitancy in practice among pro-vaccination parents; and (3) examining the association of sociodemographic characteristics (gender, age, marital status education and religious affiliation) with the difference between hesitant attitudes and hesitancy in practice among pro-vaccination parents. Methods Descriptive cross-sectional survey using an online survey that measured vaccine hesitancy among pro-vaccination parents (n = 558) whose children were in kindergarten (3–5 years), according to a variety of sociodemographic characteristics. Results A significant difference was found between the rate of hesitant attitudes and the rate of hesitation in actual vaccination among pro-vaccination and hesitant parents, where despite that 26% of the parents had hesitant attitudes, only 19% hesitated in practice [P = 0.0003]. There was also a significant difference between the rate of hesitant attitudes and the rate of hesitancy in practice among women [P = 0.0056] and men [P = 0.0158], parents between 30 and 39 years of age [P = 0.0008], traditional parents [P = 0.0093], Non-academic parents [P = 0.0007] and parents with BA degree [P = 0.0474]. Conclusion Pro-vaccination individuals may have hesitant attitudes regarding vaccines. Therefore, it is very important for health authorities to address the public's fears and concerns, including those who are classified as pro-vaccination.